Digitalisasi Ekonomi Kreatif: Transformasi Minyak Jelantah Menjadi Lilin Aromaterapi sebagai Produk Inovatif Masyarakat Ditinjau dari Filsafat Realitas Immanuel Kant - Budi Harianto; Feby Nurhalizah Siregar; Lathifah Ananda Putri; Rini Andriansi; Vany Fadilah Bastian (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
The digitalization of the creative economy has opened up significant opportunities for the community to create innovative products that have high sales value and are environmentally friendly. One interesting innovation is the use of used cooking oil as a raw material for making aromatherapy candles. Used cooking oil, which is usually discarded and pollutes the environment, can be reprocessed into products with economic value, thus supporting the principles of a circular economy. This study aims to examine the potential of processing used cooking oil into aromatherapy candles, analyze digital-based marketing strategies to increase product competitiveness in the market, and examine the meaning of transforming waste into innovative products from the perspective of Immanuel Kant's philosophy of reality. The research methods used were literature studies and field observations of used cooking oil processing practices by the community. The results show that used cooking oil-based aromatherapy candles have good business prospects, especially when combined with digital promotion through social media and marketplaces. Digitalization helps expand marketing reach, create brand identity, and attract consumers who care about environmental sustainability. From the perspective of Immanuel Kant's philosophy of reality, the transformation of used cooking oil into aromatherapy candles can be understood as a phenomenon, namely a reality that is visible in the practice of the digital creative economy. Meanwhile, the values ​​of sustainability, ethical awareness, and social meaning contained therein reflect noumena, namely the deepest reality that is not directly visible but provides direction and meaning for human actions.